Concept and punishment of Al-Qadzf / Amiruldin Md Sham - Md Sham, Amiruldin (Universiti Teknologi MARA Cawangan Pahang, 2008)
Every Muslim is supposed to guard the honour and respect of a fellowman and not bare the hidden failings of any other Muslim. If a person accuses a Muslim of adultery and cannot prove it by producing four witnesses who have seen the act being committed at the same time and at the same place, the accuser will be punished with eighty stripes. He will be considered a fasiq and as such his evidence will no longer be accepted whenever he comes forth to do so.